Jejak VOC dan Pembentukan Administratif Pemerintahan Hindia Belanda di Pontianak Kalimantan Barat - Touwe*, Sem; Sopacua, Jems (Universitas Syiah Kuala, 2023)
The purpose of the study is to reconstruct the past of the VOC (Verenigde Oouts Indiche Compagnie) activities in Pontianak, West Kalimantan in the 16th century to the attempt to occupy the area for trade purposes and then the efforts of the Dutch East Indies government to legitimize its power in the early 18th century. this paper is to reconstruct the traces of the VOC, the Dutch East Indies trading company in Pontianak, West Kalimantan. The area which was originally under the rule of the first Sultan of Pontianak Syarif Abdurrahman who pioneered the initial settlement and trading activities with traders from the archipelago and the outside world is also highlighted in this research. Therefore, the problems that will be studied in this research are: 1) What were the conditions of the early life of the people of Pontianak before the arrival of the VOC? 2) What was the attitude of the local authorities and the community when they received the VOC in Pontianak? 3) What was the main purpose of the VOC occupying the Pontianak Territory? 4) How was the process of forming the administrative area of the Dutch East Indies in Pontianak? The method used in this writing is the historical method which consists of heuristics, verification, and interpretation stages to make a deeper analysis and interpretation of the data that has been criticized and then sorted to arrive at the last stage, namely Historiography. The results of the reconstruction of the VOC traces to efforts to legitimize the power of the Dutch East Indies government in Pontianak show that due to competition in the world of trade between various traders from the archipelago and China, England, India, Portugal, Spain in Pontianak resulted in occupation and colonization by the Dutch. In addition, the occupation of the Pontianak area by the Dutch was to dispel pirates who always made traders uncomfortable from the Malacca Strait, the West Coast of Borneo, the Sulu Islands, Mindanau to the Maluku islands.